PELAKSANAAN PERLINDUNGAN KESELAMATAN DAN KESEHATAN KERJA PADA TENAGA KERJA BAGIAN PRODUKSI DI PT. WIJAYA KARYA BETON BINJAI TAHUN 2013 - henokh sembiring; lina tarigan; arfah mardiana lubis (Lingkungan dan Kesehatan Kerja, 2014)
Abstract Review the implementation of occupational safety and health protection in the sector of production PT. Wijaya Karya Beton, Binjai on 2013. This research has been done at PT. Wijaya Karya Beton, Binjai company that manufactures precast concrete. To prevent the occurrence of accidents in production management to implement safety and health protection. Under Labour Constitution. 13 In 2003, there are 3 basic aspects of occupational safety and health protection, the protection of economic, social and, technically, the implementation of the basic aspects of occupational safety and health protection is studied.This research method is descriptive qualitative research. Which describes how the implementation of occupational safety and health protection in sector  production. To collect data conducted in-depth interviews with the STAR approach and observations. The population is all part of the production workforce numbered 52 people, with Quota Random Sampling taked 35 participant. This study describes the implementation of economical form of protection has not been given appropriate overtime wages Act. Implementation of social protection in the form of social security is not well understood the contents of the program and its use by workers. Technical protection provided in the form of training, SOP, and the use of PPE, but the workers who run the SOP well only 25 people (71%) and employees who use PPE properly 20 workers (57%) of the 35 participant. Training fire and explosion hazard will be given to workers and are running well. Keywords : Labour Constitution. 13 In 2003, Protection of economic, Social and Technical.